THE TRANSCENDENTAL NATURE OF CRITICAL REFLECTION AND REFLECTION ON LIFE - Bautista Segales, Juan José (2017)
This article was written following the death of Karl-Otto Apel. The author recounts the reading process of said philosopher’s writings by Enrique Dussel and a group of his students as preparation to discuss them with the same Apel, who visited Mexico on a few occasions. Then, he approaches the pragmatic turn to demonstrate how, through the latter and the discussions with Apel himself, Dussel and the writer rethink fundamental issues in order to move forward, each in their own line of argument, with their theoretical development.